Effect of Plant Extracts on the Yield of Soybean Crop Under Different Climatic Conditions (Bangladesh Journal of Scientific and Industrial Research, 2007)
Soybean (Glycine max L., Variety PB-1) is an important oilseed crop though not extensively cultivated in Bangladesh. Five different plant extracts i.e., Bara Bishkatali leaf extract, sesame seed oil, castor seed oil, a mixture of sesame oil and neem seed oil and tobacco leaf extract were sprayed prior to pest infestation. The major insect pests encountered were the leaf roller (Sylepta derogata), pentatomid bug (Nezara viridula and Piezodorus hybneri), noctuid semilooper (Trichoplusia ni) and blue butterfly (Euchrysops cnejas). Among the applied treatments, tobacco leaf extract showed the best result followed by Bara Bishkatali leaf extract, sesame seed oil and a mixture of sesame oil and neem seed oil and castor oil. Some unidentified beneficial eurytomid, braconid, ichneumonid and encyrtid insect parasites and coccinellid predators played an important role in suppressing the pest population during the study period. The maximum yield was 36.7 maunds per acre in the BCSIR Laboratories Campus, Rajshahi but the yield was only 3 maunds per acre in the Oilseeds Cultivation Centre Patgram, Lalmonirhat. Bangladesh J. Sci. Ind. Res. 41(1-2), 73-76, 2006